2015
DOI: 10.1007/s10803-015-2644-x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Fast Mapping Predicts Differences in Concurrent and Later Language Abilities Among Children with ASD

Abstract: This study investigated whether the ability to learn word-object associations following minimal exposure (i.e., fast mapping) was associated with concurrent and later language abilities in children with ASD. Children who were poor learners at age 3½ had significantly lower receptive language abilities than children who successfully learned the new words, both concurrently (n = 59) and 2 years later (n = 53), lending ecological validity to experimental fast-mapping tasks. Fast mapping comprehension at age 3½ wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In Baron-Cohen et al's landmark study, children with ASD assigned a novel label to a toy that was their own focus of attention rather than the toy in the focus of attention of the person uttering the novel word. However, later research substantially qualified the conclusion that children with ASD cannot use social cues for word learning, finding that, in many circumstances, they can learn a name for a novel object when it is presented ostensively as part of a social interaction (e.g., Akechi et al, 2011;Luyster & Lord, 2009;McDuffie, Yoder, & Stone, 2006;Parish-Morris, Hennon, Hirsh-Pasek, Golinkoff, & Tager-Flusberg, 2007;Venker, Kover, & Ellis Weismer, 2016). For example, Luyster and Lord (2009) presented children with ASD with a mean age of 2.5 years (much younger than the 7-to 12-year-olds studied by Baron-Cohen et al) with two novel objects.…”
Section: Nounsmentioning
confidence: 96%
“…In Baron-Cohen et al's landmark study, children with ASD assigned a novel label to a toy that was their own focus of attention rather than the toy in the focus of attention of the person uttering the novel word. However, later research substantially qualified the conclusion that children with ASD cannot use social cues for word learning, finding that, in many circumstances, they can learn a name for a novel object when it is presented ostensively as part of a social interaction (e.g., Akechi et al, 2011;Luyster & Lord, 2009;McDuffie, Yoder, & Stone, 2006;Parish-Morris, Hennon, Hirsh-Pasek, Golinkoff, & Tager-Flusberg, 2007;Venker, Kover, & Ellis Weismer, 2016). For example, Luyster and Lord (2009) presented children with ASD with a mean age of 2.5 years (much younger than the 7-to 12-year-olds studied by Baron-Cohen et al) with two novel objects.…”
Section: Nounsmentioning
confidence: 96%
“…Depending on their design, novel word studies can address various phases of word learning, from initial exposure to longer-term retention (Horst & Samuelson, 2008;McMurray et al, 2012). Some studies measure fast mapping-children's ability to identify a labeled referent after only minimal exposure to a novel word and its meaning (Carey & Bartlett, 1978;McDuffie et al, 2012;Venker et al, 2016). Other studies-often conducted with school-aged children or adolescents with ASD-measure retention, consolidation, and/or generalization of new words over longer periods of time (Hartley et al, 2019(Hartley et al, , 2020Henderson et al, 2014;Norbury et al, 2010).…”
mentioning
confidence: 99%
“…To assess whether significant differences in nonverbal IQ might account for differences found in receptive and expressive language, phonological processing, and social symptom severity between the three FN/NN subgroups, we repeated these analyses using ANCOVA to control for nonverbal IQ ( Venker et al, 2016 ). To determine if the critical assumption of homogeneity of regression slopes for ANCOVA ( Tabachnick & Fidell, 2007 ) was met for each dependent variable for which there was a significant between-group difference, we examined whether there were interaction effects between subgroup and nonverbal IQ, which would violate this assumption.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies have examined the relationship of experimental word learning via fast mapping to language development in children with ASD, and neither measured retention of the novel words learned. First, in a longitudinal study of 59 preschool children with ASD, Venker, Kover, and Weismer (2016) reported that performance on a fast mapping task was positively associated with receptive and expressive language abilities concurrently at age 3 and at a follow-up at age 5 years. Although the association between word learning and expressive language at age 3 was no longer significant when analyses were adjusted for nonverbal IQ, associations held with receptive language at both age 3 and 5 years.…”
Section: Introductionmentioning
confidence: 99%